Effects of the dietary vitamin A against the effect of aflatoxin Hi on the vitamin A status of Rattus norvegicus rats - Wiryatun Lestariana, Wiryatun Lestariana (Universitas Gadjah Mada, 1999)
Background: Dichlorodiphenyl trichloroetane (DDT), polychlorinated biphenyl (PCB) and polybrominated biphenyl (PBB) are carcinogenic substances and significantly decreased liver vitamin A in the animal studies. Liver vitamin A is influenced by dietary vitamin A and the condition of the liver. Aflatoxin Bi is a carcinogenic substance like DDT, PCB and PBB. Aflatoxin Bi is the environmental exposures problem in several tropical countries and liver are the main organ targets of the carcinogenicity of aflatoxin B1.Objective: To provide more extensive description of the effects of dietary vitamin A (deficient, adequate, fourfold adequate) against the effect of aflatoxin Bi (AFB1) on the vitamin A status of rats.Methods: Vitamin A status of animals was demonstrated by concentrations of liver and serum vitamin A. The subjects consisted of fourty eight male Rattus norvegicus rats in good general condition, 1-2 months old with body weight around 62-68.5 grams, were randomly divided into 12 groups of four rats each. Rats in group I to VI which were killed at the start of the experiment and were used as the initial condition of liver and serum vitamin A concentrations for the rats in group VII to XII. Vitamin A-deficient diets were given to rats in group VII and VIII. Vitamin A-adequate diets were given to rats in group IX and X, while vitamin A-fourfold adequate diets were given to rats in group Xl and XII. Rats in group VIII, X and XII were orally treated by an aplicator with 15g of AFB1 in 0.2 ml of propylene glycol everyday for 16 weeks. While rats in group VII, IX and Xl were treated without AFB1.Results: By analysis of variance, the results showed that the effects of interaction of dietary vitamin A and AFB1 demonstrated a very significant effect (p<0.001) on liver vitamin A and significant effect (p<0.05) in serum vitamin A concentrations. Dietary vitamin A itself demonstrated a very significant effect (p<0.001) in serum and liver vitamin A concentrations. While AFB1 demonstrated a significant effect (p<0.05) in liver vitamin A and significant effect (p<0.001) on liver vitamin A concentarations.Conclusions: Vitamin A status of rats given aflatoxin Bi were not only influenced by dietary vitamin A but also by allatoxin Bi treatment.Key words: dietary vitamin A - aflatoxin Bi - serum vitamin A -liver vitamin A - Rattus norvegicus rats